Exploring the Landscape of Big Data Analytics in Financial Decision Making - Mahmudi, Bambang (Penelitian dan Pengembangan Ilmu, 2024)
Big Data analysis has become an integral part of financial decision making in the modern corporate context. In an increasingly complex and competitive environment, a deep understanding of the factors that influence the success of Big Data analysis is critical. This research aims to investigate the role of variables such as data quality, data security, technology infrastructure, data analysis skills and expertise, leadership and organizational culture, regulations and compliance, and clear business objectives in corporate financial decision making. Using a literature analysis approach, we found that high data quality, strong data security, adequate technology infrastructure, high data analysis skills and expertise, supportive leadership, regulatory compliance, and clear business objectives each contribute positively to the effectiveness of Big Data analysis in supporting financial decision making. These findings highlight the importance of holistic integration of these factors in efforts to improve corporate financial decision-making processes.